PERBANDINGAN ber- BAHASA INDONESIA DAN ba- BAHASA SUMBAWA DIALEK TALIWANG - Burhanuddin, Burhanuddin Burhanuddin (English Department FBS UNP, 2019)
This paper aims to explain the combined power, morphophonemic processes, meanings, and similarities and differences of affix ber BI and ba- BSDT. Methodologically, data collection uses observation and introspection methods, while data analysis using substitution, expansion, and contrastive methods. The results of the study that ber- BI and ba- in BSDT can attach to the basic nouns, adjectives, verbs and pronominal but both have differences in morphophonemic processes and meanings. For example, the form berbapak ‘has what is in the basic form’ in BI does not fit ba- in BSDT, since it is realized as a rabapak (using prefix ra-). Similarly, to express the meaning of 'a collection consisting of such amount in its basic form', as in the form of berdua, bertiga, berempat, and so on (except the unified form) in BI does not correspond to the form ba- in BSDT because it uses prefix ka-, for example in the form kaduaq, kateluq, and so on.